Tindak Tutur dalam Debat Calon Presiden Republik Indonesia 2014 - Silvia Ratna Juwita (Indonesian Journal of Applied Linguistics Review, 2017)
This study aimed to describe and assess the speech acts in the Republic of Indonesia Presidential Debate in 2014 on June 15, 2014 with the theme of Economic Development and Social Welfare. This research is a qualitative descriptive study discourse analysis. Data of this study were (1) assertive speech acts in the presidential debate in 2014; (2) directive speech acts in a presidential debate in 2014; (3) The expressive speech acts in a presidential debate in 2014; (4) commissive speech acts in a presidential debate in 2014; and (5) the declaration speech acts in the 2014 presidential debate.This research is the source of debate Republican candidate for President in 2014 in the form of speech acts revealed by the 2014 Republican Presidential candidate in the debate. The findings of this study are illocutionary speech acts are used in every speech from both presidential candidates in the 2014 presidential debate and comparison of speech of both presidential candidates.This study is recommended to add insight to the general public, as a consideration of teaching materials for colleges and high schools